Stress and Anxiety during the Covid-19 Pandemic: Experiences of Special Needs and Learning Support Educators - Mpho Mthembu; Michelle Finestone (E-Journal of Humanities, Arts and Social Sciences)
The purpose of this study was to investigate the factors that contributed to stress and anxiety in special needs and learning support educators during the COVID-19 pandemic. The study used qualitative methodology, incorporating semi-structured interviews, a qualitative questionnaire, and a focus group discussion for data collection. Ten special education and learning support teachers from special schools, and full-service schools in the Gauteng province, in South Africa were sampled for the study. Using interpretive phenomenology to analyse the data gathered for this study, it was discovered that special needs and learning support educators experienced stress and anxiety during the Covid-19 pandemic because of (a) an increase in workload; (b) adapting traditional face-to-face methods of teaching to online education; (c) teacher and parent collaboration, and (d) implementing COVID-19 regulations in a special needs classroom. The study proposes several recommendations, including the enhancement of teacher preparation for online pedagogical methods, the provision of psychological support services, the improvement of parental communication channels, and the promotion of curricular flexibility. Emphasis is placed on appropriate resource allocation, professional development workshops, and the implementation of online counseling services to identify challenges. This study contributes to the body of knowledge regarding the coping mechanisms employed by SETs and LSEs during crises such as the COVID-19 pandemic. Furthermore, it underscores the need for comprehensive support systems and adequate resource provision to enable educators to effectively perform their roles under adverse circumstances.